Tp51. Tp051 Covid: Lung Infection, Multiorgan Failure, and Cardiovascular 2021
DOI: 10.1164/ajrccm-conference.2021.203.1_meetingabstracts.a2631
|View full text |Cite
|
Sign up to set email alerts
|

Are Hospitalized Patients with Chronic Lung Disease and COVID-19 Infection at a Greater Risk of Dying? Single Cohort Experience

Abstract: Background: Given the devastating impact that COVID-19 can have on the lung, it is reasonable to fear for patients with underlying chronic lung conditions. Recent studies have shown that there is an excess risk of contracting the infection, as well as developing severe symptoms and worst outcomes for some of these conditions. We present a single center experience of the characteristics and outcomes of patients admitted due to with confirmed SARS-CoV-2 infection and chronic lung disease. Methods: Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…COVID-19 status in all was confirmed by SARS-Cov-2 RT-PCR. Of the nineteen included studies, eight [ 15 , 16 , 18 , 24 , 27 , 29 , 30 , and 33 ] were from North America, five [ 17 , 22 , 26 , 28 , and 31 ] from Asia, five [ 19 21 , 23 , and 25 ] from Europe, and one [ 32 ] from South America. Eighteen [ and 15 – – 33 ] were cohort studies, while one [ 21 ] was cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 status in all was confirmed by SARS-Cov-2 RT-PCR. Of the nineteen included studies, eight [ 15 , 16 , 18 , 24 , 27 , 29 , 30 , and 33 ] were from North America, five [ 17 , 22 , 26 , 28 , and 31 ] from Asia, five [ 19 21 , 23 , and 25 ] from Europe, and one [ 32 ] from South America. Eighteen [ and 15 – – 33 ] were cohort studies, while one [ 21 ] was cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies reported in favor of poor prognosis of COVID-19 in asthmatic patients [ 18 , 22 , 26 , 28 , 31 ]. However, other scientific observations have reported conflicting results [ 15 17 , 19 21 , 23 25 , 27 , 29 , 30 , 32 , 33 ]. Our meta-analysis did not identify asthma as a significant risk factor in producing high severity and mortality from SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%